1978
DOI: 10.1007/bf01317848
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ascorbic acid on infection of chick-embryo ciliated tracheal organ cultures by coronavirus

Abstract: Chick embryo tracheal organ cultures showed increased resistance to infection by a coronavirus after exposure to ascorbate, while chick respiratory epithelium and allantois-on-shell preparations showed no increase in resistance to infection by an influenza virus or a paramyxovirus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
2

Year Published

1981
1981
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(66 citation statements)
references
References 18 publications
1
63
0
2
Order By: Relevance
“…The first finding was the positive effect of AA on the trachéal lesions at 10 days after challenge. This is in agreement with the observations of Atherton et al (1978) that AA increases the resistance of the trachea to IB infections in an organ culture system. The small number of birds in the same groups with air sacculitis at 14 days may be caused by the relatively mild trachea lesions by which the risk of secondary E. coli infections was lowered (although bacterial culturing not was included in the experiment, some affected air sacs were cultured to demonstrate the presence of E. coli).…”
supporting
confidence: 93%
See 1 more Smart Citation
“…The first finding was the positive effect of AA on the trachéal lesions at 10 days after challenge. This is in agreement with the observations of Atherton et al (1978) that AA increases the resistance of the trachea to IB infections in an organ culture system. The small number of birds in the same groups with air sacculitis at 14 days may be caused by the relatively mild trachea lesions by which the risk of secondary E. coli infections was lowered (although bacterial culturing not was included in the experiment, some affected air sacs were cultured to demonstrate the presence of E. coli).…”
supporting
confidence: 93%
“…Moreover, viral infections are associated with a rapid decrease in circulating AA concentrations (Beisel, 1982) suggesting that whilst the AA concentration may be optimal for healthy birds, it is suboptimal during periods of infection. Atherton et al (1978) found that chicken-embryo tracheal organ cultures with supplemented AA were up to 15 times more resistant to infections with infectious bronchitis virus (IBV) than the controls. Increased amounts of AA in the feed of Leghorn-type chickens reduced the incidence of pericarditis or death following air sac challenge with Escherichia coli.…”
Section: Introductionmentioning
confidence: 99%
“…En estudios con animales se ha demostrado que la vitamina C aumenta la resistencia a la infección causada por el coronavirus y también modifica la susceptibilidad a la infección 26 . Nathens et al 27 administraron 1 g de ácido ascórbico cada 8 h combinado con vitamina E oral durante 28 días en 594 pacientes quirúrgicamente críticos y encontraron una incidencia significativamente menor de lesión pulmonar aguda y fallo multiorgánico. En un estudio clínico descrito por Sawyer et al 28 se emplearon grandes dosis i.v.…”
Section: Neumonía Y Sdraunclassified
“…The more likely explanation though may be that due to the high case fatality of Nipah, controls were able to report exposures more completely than cases. While it is possible that sour fruits with high vitamin C content may have a protective effect against viral infection through ascorbic acid, there was no observed association between eating fruit and Nipah infection in the multivariable model of best fit (Atherton et al 1978). …”
Section: Discussionmentioning
confidence: 98%